2021
DOI: 10.1155/2021/8661162
|View full text |Cite
|
Sign up to set email alerts
|

Is Electroacupuncture an Effective and Safe Treatment for Poststroke Depression? An Updated Systematic Review and Meta-Analysis

Abstract: Objective. To observe and compare the efficacy and safety of electroacupuncture and antidepressants in the treatment of poststroke depression (PSD) using a meta-analysis method. Methods. The VIP, CNKI, Wanfang, CMB, Embase, PubMed, and Cochrane databases were searched. All randomized controlled trials (RCT) on electroacupuncture treatment of PSD were searched and further screened. Meta-analysis was performed on electroacupuncture and western medicine for PSD to explore the difference in efficacy between electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In all, 19 studies were excluded due to the following reasons: No necessary sample data ( n = 8), Other outcomes ( n = 5), Other reviews ( n = 4), and Other languages ( n = 2) ( Figure 1 ). Thus, 17 studies were included in the umbrella review (Yi et al, 2010 ; Eng and Reime, 2014 ; Ren et al, 2015 ; Tan et al, 2015 ; Feng et al, 2018 , 2022 ; Jin et al, 2018 ; Wang et al, 2018 , 2021 ; Liu et al, 2019 , 2021 ; Li et al, 2020 ; Cai et al, 2021 ; Lee et al, 2021 ; Zhang et al, 2021a , b ; Guo et al, 2022 ). Study characteristics and quality ratings of 17 meta-analyses/systematic reviews were summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In all, 19 studies were excluded due to the following reasons: No necessary sample data ( n = 8), Other outcomes ( n = 5), Other reviews ( n = 4), and Other languages ( n = 2) ( Figure 1 ). Thus, 17 studies were included in the umbrella review (Yi et al, 2010 ; Eng and Reime, 2014 ; Ren et al, 2015 ; Tan et al, 2015 ; Feng et al, 2018 , 2022 ; Jin et al, 2018 ; Wang et al, 2018 , 2021 ; Liu et al, 2019 , 2021 ; Li et al, 2020 ; Cai et al, 2021 ; Lee et al, 2021 ; Zhang et al, 2021a , b ; Guo et al, 2022 ). Study characteristics and quality ratings of 17 meta-analyses/systematic reviews were summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, two related reviews were published. One was an update of a meta-analysis of EA for post-stroke depression in 2018 (19 trials) (18), which indicated that in comparison with antidepressants, EA has a similar effect in improving depression symptoms and shows better safety in post-stroke depression patients. Another systematic review focused on the neuroimaging effects of acupuncture (including EA) in depression (10 trials of EA) (65).…”
Section: Discussionmentioning
confidence: 99%
“…A review in 2018 exploring the overall efficacy of acupuncture (both EA and MA) on depression found weak evidence suggesting that the efficacy and safety of acupuncture was no less than that of antidepressants, and that acupuncture combined with antidepressants may have better efficacy than antidepressants alone (15). Some reviews focusing on EA for specific subtype of depression, such as PSD (16) postpartum depression (17,18) found EA had similar efficacy to other therapy and better safety. But most of these reviews did not carry subgroups comparison and the evidence grade was low mainly due to lack of included studies.…”
Section: Introductionmentioning
confidence: 99%
“…Moxibustion facilitates antidepressant effects by promoting the brain’s uptake of tryptophan and converting tryptophan metabolism to 5-HT ( 70 ). Electroacupuncture can enhance the body’s defense function, inhibit the secretion of inflammatory factors after stroke, and thus reduce the treatment of injury PSD ( 71 ). Acupuncture points on the abdomen can stimulate signals to the gut-brain through the abdominal wall, thus exerting the abdominal-brain correspondence regulation mechanism to treat PSD ( 72 ).…”
Section: Discussionmentioning
confidence: 99%